INTERMITTEN AERATION IMPACT ON SUBMERGED AERATIED BIOFILTER PERFORMANCE TO WASTEWATER WITH GREYWATER CHARACTERISTIC - YULIANTO (NIM 25305002), ANDIK
Greywater contribute 50-80% wastewater generation of domestic wastewater, but contain less organic concentration than blackwater. The characteristic of greywater is good for reuse purposes after its treatment. One of treatment method that can be applied for greywater treatment is submerged aerated biofilter (SAB), which shows better performance for light organic wastewater compared to activated sludge method. Problem in SAB usage is expensive operation cost. Cost problem can be solved by using intermittent aeration rather than continous aeration (Schulz, 2001). But Schulz (2001) did not mention about effect intermittent aeration on reactor performance. This research highlights this part empirical observation for comparing performace SAB reactor with continous aeration and intermitten aeration. Three reactors were set up to run parallel treating artificial greywater wastewater (sucrosa) with SCOD concentration similar to 300 mg/l, using bioball media. The reactors were run on batch and continous method. For continous mode the reactors run upflow with liquid flowrates of 0,048 m3/d and air flowrate of 3,5 L/h. Reactor 1 (R1) were set up with aeration condition 2 hous on and 2 hours off (2-2), R2 4-4, and R3 continous aeration. The result indicates that the removal efficiency for continous mode R1 was 83%, R2 81%, and R3 87%. But three reactors did not show differences on removal rate both batch and continous mode, although it shows small differences in DO increasing, and amonium removal. It can be concluded that intermittent aeration can replace continous aeration with small differences in SAB performance.